NILAI PENDIDIKAN KARAKTER DALAM NOVEL BULAN TERBELAH DI LANGIT AMERIKA - Lastaria, NFN; Widya, NFN (SUAR BETANG, 2019)
Character Education Values in Novel Month After the American Sky. Talking about novel issues and character values that a good novel is a novel that has many benefits or has many good values. Therefore, researchers chose the novel as a study material. Novels taken as study material are novels written by Hanum Salsabiela Rais and Rangga Almahendra with the title "Split Moon in the Sky of America". From the analysis there are 19 character values contained in the novel, namely (a) religious, (b) honest, (c) responsible, (d) healthy lifestyle, (e) discipline, (f) hard work, (g) self-confidence, (h) logical thinking (critical, creative, and innovative), (i) independent, (j) curiosity, (k) self-conscious, (l) polite, (m) democratic, (n) nationalist, (o) pluralist, (p) intelligent, (q) helpful, (r) resilient, and (s) action oriented.